2009
DOI: 10.1103/physrevlett.103.010404
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Liquid Crystals in an Imbalanced Fermi Gas: Fluctuations and Fractional Vortices in Larkin-Ovchinnikov States

Abstract: We develop a low-energy model of a unidirectional Larkin-Ovchinnikov (LO) state. Because the underlying rotational and translational symmetries are broken spontaneously, this gapless superfluid is a smectic liquid crystal, that exhibits fluctuations that are qualitatively stronger than in a conventional superfluid, thus requiring a fully nonlinear description of its Goldstone modes. Consequently, at nonzero temperature the LO superfluid is an algebraic phase even in 3d. It exhibits half-integer vortex-dislocat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
218
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(227 citation statements)
references
References 32 publications
8
218
1
Order By: Relevance
“…Consequently, as was originally anticipated by Shimahara [110], and was demonstrated in our recent work [112], to be explored in greater detail below, their Goldstone modes are qualitatively "softer", and therefore exhibit far stronger fluctuations. These can either completely destabilize the (otherwise energetically stable) FFLO state, or can qualitatively modify its meanfield form and properties.…”
Section: Fluctuation In the Fflo Statesmentioning
confidence: 71%
See 2 more Smart Citations
“…Consequently, as was originally anticipated by Shimahara [110], and was demonstrated in our recent work [112], to be explored in greater detail below, their Goldstone modes are qualitatively "softer", and therefore exhibit far stronger fluctuations. These can either completely destabilize the (otherwise energetically stable) FFLO state, or can qualitatively modify its meanfield form and properties.…”
Section: Fluctuation In the Fflo Statesmentioning
confidence: 71%
“…However, given the extensive 45-year history of the topic, it is astounding that the equally basic complementary question of the nature of Goldstone modes description and their fluctuations within the FFLO states received so little attention, [110,111] until our study of the problem, reported in a recent Letter [112]. From the general symmetry principles the FFLO states' lowenergy phenomenology is expected to be significantly richer than that of a homogeneous fully gapped superconductor, whose low-energy phenomenological (GinzburgLandau and xy-model) description long predated the microscopic theory by BCS [99][100][101].…”
Section: Fluctuation In the Fflo Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…FFLO states have been proposed over the years for different types of superconducting materials, most recently in the phase diagram of the heavy fermion superconductor CeCoIn 5 at finite magnetic fields, 14 although the experimental evidence for them is weak (at best). There are also recent theoretical proposals for FFLO-type states in cold atomic fermionic systems with unbalanced populations, 15 and in quantum wires of multi-valley semiconductors. 16 In the conventional theory of FFLO states one assumes a BCS-type system (a Fermi liquid) in which the spin up and down Fermi surfaces are split by the Zeeman interaction with an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments [6] have explored two-species, attractively-interacting fermionic atomic gases in a quasi one-dimensional (1D) geometry, of interest since the regime of stability of the FFLO state is theoretically predicted [7,8] to be much wider than in the 3D case [9] (at least within the simplest mean-field approximation [10]). These experiments showed a remarkable quantitative agreement between experiment and theory for the local densities n σ (z) of the two species (σ =↑, ↓) of atoms within a theoretical approach that combined exact BetheAnsatz analysis of an infinite 1D gas with the local density approximation (LDA) to handle the spatial variation of the trap.…”
Section: Introductionmentioning
confidence: 99%